2010
DOI: 10.1007/s10344-010-0469-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of seed availability on habitat use by a specialist seed predator

Abstract: Space-use patterns of seed predators are strongly affected by spatiotemporal variation in the abundance of different tree seeds, their major food source. However, most studies have measured relationships between overall food availability and space use, and there are few cases where effects of different food resources have been explored. We studied the effects of two food resources, Norway spruce and silver fir seeds, on space and habitat use in red squirrel in a subalpine conifer forest from 2000 to 2006. Fir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…Each year between 26 July -9 August, the new (current year) maturing cones were counted in the canopy of sample trees of all conifer species to estimate food availability. Methods are described in detail elsewhere (Salmaso et al 2009;Di Pierro et al 2011). Based on species-specific energy values per cone (kJ/cone) and data on tree species composition and density (Salmaso et al 2009), these counts allowed us to estimate the average yearly tree seed-energy production in each study area ( Table 1).…”
Section: Study Areas and Food Availabilitymentioning
confidence: 99%
“…Each year between 26 July -9 August, the new (current year) maturing cones were counted in the canopy of sample trees of all conifer species to estimate food availability. Methods are described in detail elsewhere (Salmaso et al 2009;Di Pierro et al 2011). Based on species-specific energy values per cone (kJ/cone) and data on tree species composition and density (Salmaso et al 2009), these counts allowed us to estimate the average yearly tree seed-energy production in each study area ( Table 1).…”
Section: Study Areas and Food Availabilitymentioning
confidence: 99%
“…Thus, if foraging would be determined mainly by (i) rate of energy-intake, (ii) cone morphology, in particular the reduced amount of protective tissue (Molinari et al 2006), or (iii) temporal availability of the food source, red squirrels should strongly select fir seeds between mid August and mid October, when they are available in the tree canopy. However, squirrels prefer Norway spruce over fir seeds in all seasons and years and fir seed consumption is limited, occurring to some extent only in years with spruce seed-crop failure (Di Pierro et al 2011). Since previous studies on squirrel food choice have demonstrated that tannins and terpenes contained in seeds and/or cone scales of some tree species induce animals to reduce consumption of these food items, we have considered the hypothesis that avoidance of fir seeds is caused by higher ratio of some PSMs on dry mass or by higher concentrations of specific PSM(s) in silver fir seeds and/or cones.…”
Section: Parametermentioning
confidence: 98%
“…Our previous work, including observations of feeding behaviour Di Pierro et al 2011), showed that also red squirrels prefer spruce and avoid fir seeds.…”
Section: Fir Versus Sprucementioning
confidence: 99%
See 1 more Smart Citation
“…Given the general lack of understanding of how rodent populations are affected by high interannual variation in conifer seed production, and the significance of their population fluctuations for structuring bird and insect population dynamics (McShea 2000;Ostfeld & Keesing 2000), long-term data sets on annual conifer seed production and intensive rodent trapping can provide valuable insights into this important interaction in forest ecosystems. The effect of conifer masting on consumer population dynamics, and its implications for the predator satiation hypothesis and the evolution of masting, have recently been documented for North American (Tamiasciurus hudsonicus) and Eurasian (Sciurus vulgaris) red squirrels, two dominant pre-dispersal seed predators (Boutin et al 2006;Wauters et al 2008;Fletcher et al 2010;Di Pierro et al 2011;Archibald et al 2012). However, the efficacy of this hypothesis for post-dispersal seed predators is unclear.…”
Section: Introductionmentioning
confidence: 99%